Tectonism in Architecture, Design and Fashion: Innovations in Digital Fabrication as Stylistic Drivers. (2nd November 2017) - Schumacher, Patrik
Abstract : After 'foldism' and 'blobism' comes 'tectonism' – a new branch of the epochal style of parametricism that allows greater expressive and formal variety. It is made possible by an evolving range of digital tools for structural form‐finding and physics analysis, linked directly to fabrication. AsPatrik Schumacher, principal of Zaha Hadid Architects, underlines, these do not remove the need for architects to collaborate with engineers and fabricators, but they do enable them to acquire more reliable intuitions about the logics of these other disciplines. This can only enhance their capacity to produce works that successfully combine communication and social functionality with technical integrity.